Externalização na criação do conhecimento organizacional : caso das agências de publicidade - Ferraz, Janaynna de Moura (2015)
Knowledge management becomes paramount to the survival of contemporary organizations now committed to converge the collective knowledge for a common purpose to the group. Consecrated literature mentions that among the faces of knowledge management, there is the theory of creation of corporate knowledge, presented in spiral form in a process that culminates in four possible modes of knowledge conversion. Although it declared the relevance of knowledge creation today, one can see that little is understand how it occurs in the practice. Thus, this research aimed to investigate the role of externalization, which is a form of knowledge conversion, given its relevance in the process of organizational knowledge creation and it will investigate the agencies of advertising, classified as knowledge-intensive business services. The search strategy was a single case study with six little cases (advertising agencies), the unit of analysis was the very phenomenon resulting from the spiral path of corporate knowledge. The approach was descriptive and exploratory and research went into a sequence of two phases. The first phase was a qualitative in a descriptive approach. Data were collected through an online questionnaire answered by employees of Sergipe advertising agencies and in parallel through an e-focus group with the owners / managers of these organizations. The second phase, qualitative and exploratory, used the data collection of the first phase added to your specification, investigating new perspectives of the problem through the crossing of evidence to the theory of knowledge creation. Data were treated with simple descriptive statistics and content analysis whose classification was categorized in terms. Among the main results, it is emphasized that externalization, in addition to calls for the theory, not only has an important role, beyond, its role is decisive, so that it is believed that the absence of externalization implies the absence of management knowledge in organizational practice. This research intends that this research will contribute to the understanding of knowledge management, offering new horizons for the theory and practice in organizations.